2013
DOI: 10.1111/j.1365-4632.2012.05822.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin diseases among schoolchildren in Ghana, Gabon, and Rwanda

Abstract: The prevalences of skin diseases among African schoolchildren were high. Skin infections such as tinea capitis and pyoderma predominated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
60
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 46 publications
10
60
2
Order By: Relevance
“…Environmental factors such as insect bites and parasitic infections play also a major rôle in the etiology of pediatric skin conditions. Thus Hogewoning and Kaliaperumal noted that infections were the highest in their studies from Ghana, Gabon and South India.They attributed it to poor hygiene, low socioeconomic levels and the prevalence of poor health awareness[12] [13].…”
mentioning
confidence: 99%
“…Environmental factors such as insect bites and parasitic infections play also a major rôle in the etiology of pediatric skin conditions. Thus Hogewoning and Kaliaperumal noted that infections were the highest in their studies from Ghana, Gabon and South India.They attributed it to poor hygiene, low socioeconomic levels and the prevalence of poor health awareness[12] [13].…”
mentioning
confidence: 99%
“…Even though it is not in line with the current finding; a similar study in Ethiopia showed that the prevalence of T.tonsurans in the rate 5.8% & 18.4% [9,21]. T.tonsurans had been reported in developing countries such as Kenya and other sub-Saharan countries as among the most common agent followed to M. canis and due to its ubiquitous in nature, abundance among human carriers, and Social phenomena of today on the continent could explain T.tonsurans are circulating in the population [20][21][22][23]26,27].…”
Section: Discussionmentioning
confidence: 99%
“…tonsurans being the most predominant dermatophyte due its ubiquitous in nature and abundance among human carriers [20,26,27]. This could show that T.tonsurans is spreading in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%